TECHNOLOGY FOR INCREASING THE STRENGTH QUALITY INDICATOR LEVELS OF CADETS - Abdullaev, Akmal (Журнал иностранных языков и лингвистики, 2022)
In this scientific article, the research conducted on the growth parameters of the physical fitness level of cadets is considered. The general difference between the groups and the dynamics of changes in the strength quality indicator were observed.